2016
DOI: 10.1002/etc.3609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe (III) on Pseudokirchneriella subcapitata at circumneutral pH in standard laboratory tests is explained by nutrient sequestration

Abstract: The complex chemistry of iron (Fe) at circumneutral pH in oxygenated waters and the poor correlation between ecotoxicity results in laboratory and natural waters have led to regulatory approaches for iron based on field studies (US Environmental Protection Agency Water Quality Criteria and European Union Water Framework Directive proposal for Fe). The results of the present study account for the observed differences between laboratory and field observations for Fe toxicity to algae (Pseudokirchneriella subcapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This finding suggests either that precipitated barium sulfate was more toxic than dissolved barium or that other, indirect, mechanisms of toxicity were at play in the presence of the precipitate that contributed to the overall algal response. Such indirect mechanisms of toxicity have been observed for iron(III) precipitation in freshwater algal tests in which phosphorus becomes limiting in the test media with increased iron hydroxide precipitation (Arbildua et al ). In the algal tests of the present study conducted in SSW in which precipitation of barium sulfate occurred, phosphorus concentrations also decreased with increasing barium concentrations but did not decrease significantly ( p < 0.05) until concentrations of 100 mg Ba/L or more, at which point only 9 to 25% of the initial phosphorus remained (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…This finding suggests either that precipitated barium sulfate was more toxic than dissolved barium or that other, indirect, mechanisms of toxicity were at play in the presence of the precipitate that contributed to the overall algal response. Such indirect mechanisms of toxicity have been observed for iron(III) precipitation in freshwater algal tests in which phosphorus becomes limiting in the test media with increased iron hydroxide precipitation (Arbildua et al ). In the algal tests of the present study conducted in SSW in which precipitation of barium sulfate occurred, phosphorus concentrations also decreased with increasing barium concentrations but did not decrease significantly ( p < 0.05) until concentrations of 100 mg Ba/L or more, at which point only 9 to 25% of the initial phosphorus remained (data not shown).…”
Section: Resultsmentioning
confidence: 81%
“…Lastly, operationally defined dissolved iron has been found to correlate strongly with DOC levels in natural waters (Allard et al, 2011 ; Fujii et al, 2008 ), but the complexation of iron by DOC is associated with lower bioavailability (Arbildua et al, 2017 ). Complexed soluble iron can be recovered by other methods such as the acid‐soluble method applied in these experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting to understand the potential ramifications of the findings of the present study given that toxicity data from the literature comes from a wide range of colloidal iron ages (in many cases not specified). For example, Biesinger & Christensen ( 1972 ) derived chronic 16% effect concentration values for Daphnia magna after exposure to 4‐day‐old iron suspensions, whereas Arbildua et al ( 2017 ) and Sykora et al ( 1972 ) used 3‐ and ~2‐h‐old suspensions in their experiments, respectively. Yoshida et al ( 2006 ) demonstrated how iron(III) uptake in diatoms substantially decreased when comparing treatments with direct addition of Fe 3+ versus iron colloids aged for 1 and 3 days, and up to 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of the algal tests, the pH was highest in the controls and decreased as Fe concentrations increased. Tests performed by Arbildua et al (2017) at CIMM with algae exposed to Fe achieved significantly better pH control through the use of MES and HEPES buffers. In the tests with C. dubia and P. promelas using buffers, average pH remained relatively stable over the course of the exposures at ±0.2 SU of target pHs.…”
Section: Water Chemistrymentioning
confidence: 99%